Hacia una nueva conceptualización de los servicios públicos - Hernández Flores, Sonia (2010)
This thesis to qualify as a lawyer, aims to introduce the new conceptual guidance in moving the concept of public service that has changed from its original conception, in which the monopolization of state, was a substantial element : subjective orientation, to a new concept which takes into account the public nature of the activity directed at meeting basic needs for administrators, without reference to the person involved, it can be, sometimes the state, now the particular: objective orientation. This new orientation is observed in highly developed countries, which shred in practice, liberal theorists of Latin America who are in favor of less government more market, which involves the disappearance of public service. In the new theoretical structure, there is also the presence of a set of principles aimed at establishing a more dynamic, productive, including public service, efficiency and governance. We propose that an efficient public service, legitimizes the power, and is there a direct relationship between public service - efficiency and governance. In the process of analysis indicates that the term public service in Peru, is born of the Act, unlike France, which rises from the case